Studi kasus pemberian kredit usaha kecil dengan jaminan tanah belum bersertifikat pada PT. Bank Sumut Medan - Shah, Muhammad Rahmaddian; Kamello, Tan; Andriati, Syarifah Lisa (Universitas Medan Area, 2024)
This study analyzes the legal implications and risk mitigation strategies in the use of uncertified land as credit collateral at PT Bank Sumut. The bank plays an important role in supporting local economic growth through the provision of credit to SMEs, but faces major challenges related to the legality of uncertified land. The research method used is normative juridical, supported by empirical data to examine relevant laws and regulations, such as Law Number 10 of 1998 concerning Banking and Law Number 4 of 1996 concerning Dependent Rights. The results of the study show that land that has not been certified as collateral increases legal risks for banks. Bank Sumut has developed a comprehensive credit assessment strategy and mitigation measures, such as independent assessments and credit restructuring, to mitigate the associated risks. In conclusion, this practice requires the strict application of the prudential principle.